357 TAK-573, an anti-CD38–attenuated interferon alpha (IFNα) fusion protein (Attenukine™), has demonstrated IFNα receptor (IFNAR) pathway modulation in patients with relapsed/refractory multiple myeloma. (9th November 2020) - Collins, Sabrina; Joshi, Adarsh; Shen, Lei; Das, Subhasree; Suryanarayan, Kaveri; Bottino, Dean; Li, Cheryl; Curley, Michael; Wang, Dannie; Abadier, Michael; Larson, Ryan; Parot, Xavier
Abstract : Background: TAK-573, a humanized, anti-CD38, IgG4, monoclonal antibody genetically fused to two attenuated IFNα2b molecules, was designed for targeted delivery of attenuated IFNα2b to CD38 expressing (CD38+) cells, utilizing a unique epitope of CD38 that does not compete with current anti-CD38 therapies. Preclinical evaluation of TAK-573 confirmed activation of type I IFN signaling in CD38+ cells inducing direct anti-proliferative effects on multiple myeloma (MM) cells and direct and indirect immune cell activation. Here we provide the preliminary analyses of the pharmacodynamic data currently available from the ongoing Ph I/II TAK-573-1501 clinical study in patients with relapsed/refractory MM (NCT03215030 ). Methods: Peripheral blood (PB) and bone marrow (BM) aspirates were collected from patients at pre- and post-dose time points for exploratory biomarker analyses. CD38 receptor occupancy (RO) and receptor density (RD) were determined using a 9-color flow cytometry assay. Whole transcriptome sequencing of bulk RNA was performed and analyzed to assess the type I IFN gene signature. Serum samples were analyzed using Olink's Proximity Extension Assay Immuno-Oncology panel to measure changes in cytokine levels. Mass cytometry-based immunophenotyping was utilized to characterize changes in immune cell prevalence and activation status of cryopreserved cells. Results: Administration of TAK-573 resulted in a dose dependent increase in CD38 RO of PB-derived immune cells with saturation detected 4 hours after the end of infusion (EOI) at doses ≥ 0.2 mg/kg. The duration of saturation was dose dependent with doses ≥ 0.75 mg/kg saturating CD38 RO through 24 hours. All dose levels tested resulted in increases in the type I IFN gene signature at 24 hours. Consistent with CD38 being an IFN stimulated gene, TAK-573 treatment resulted in CD38 RD increases most notably on NK cells, but also on other CD38+ cells including MM cells. Circulating levels of IFN-associated cytokines were also elevated, with maximal induction 4 hours after the EOI. CD8+ T-cells in BM showed increased CD69 expression in 7 of 9 patients analyzed, 3 of whom also showed increases in both IFNγ and granzyme B positivity suggesting TAK-573 treatment results in increased BM cytolytic CD8+ T-cells, in a subset of patients. Conclusions: These preliminary biomarker data indicate that TAK-573 is a pharmacologically active molecule that mediates its effect through IFNAR pathway modulation. Additional data are being collected to further refine the mechanism of action (Image 1), which will inform the recommended phase 2 dose and optimal schedule of administration for the development of TAK-573. Trial Registration: ClinicalTrials. gov: NCT03215030 Ethics Approval: The TAK-573-1501 study is approved by WIRB-Copernicus Group, University of Nebraska Medical Center, Dana Farber Cancer Institute and Advarra IRBs.